The Effect of Acceptance and Commitment Therapy (ACT) on Test Anxiety and Psychological Well-being of High School Students - Saeed Habibollahi; Ahmad Abedi; Farah Naderi; Mohammad Mahdi Mazaheri (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2019)
Aim and Background: Test anxiety is one of the most common anxieties in educational environments, which, in addition to negative effects on academic performance, can lead to a reduction in psychological well-being among students. Therefore, the purpose of this study was to investigate the effect of acceptance and commitment Therapy (ACT) on test anxiety and psychological well-being of high school students. Methods and Materials: This study was a semi experimental with a pre-test and post-test design and control group. The statistical population included all boy students in high school of Najaf Abad city in the school year 2013-2014. Sample size includes 60 students (each group 30 person) that were selected by multistep cluster sampling method. Both groups completed the Sarason's Test Anxiety Scale (TAS) and Reef's Psychological Well-Being Scale (PWBS) as pre-test and post-test. Data was analyzed by multivariate analysis of covariance (MONCOVA) method and using the SPSS software. Findings: The results of MONCOVA showed that there is a significant difference between post-test scores of experimental and control groups (p<0.001, F= 44.80 ) . In the other hand, ACT led to significant decrease test anxiety (F= 33.17, p<0.001 ) and significant increase psychological well-being (F= 27.26, p<0.001). Conclusions: The results showed ACT method is effective in decrease test anxiety and increase psychological well-being of students.